2002
DOI: 10.1128/aem.68.12.6121-6128.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Nitrate-Reducing Community from Unplanted and Maize-Planted Soils

Abstract: Microorganisms that use nitrate as an alternative terminal electron acceptor play an important role in the global nitrogen cycle. The diversity of the nitrate-reducing community in soil and the influence of the maize roots on the structure of this community were studied. The narG gene encoding the membrane bound nitrate reductase was selected as a functional marker for the nitrate-reducing community. The use of narG is of special interest because the phylogeny of the narG gene closely reflects the 16S ribosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 35 publications
12
138
3
1
Order By: Relevance
“…However, this did not mean that these nirKharboring denitrifiers belonged to Rhizobiales or Burkholderiales, since the nirK phylogeny was incompatible with the 16S rDNA phylogeny (Heylen et al, 2006;Jones et al, 2008;Philippot et al, 2002;Yoshida et al, 2009). Our results showed that over 80% of NirS clones distributed in clusters I and VI (unknown branch), cluster II (Rhodobacterales).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commmentioning
confidence: 59%
See 1 more Smart Citation
“…However, this did not mean that these nirKharboring denitrifiers belonged to Rhizobiales or Burkholderiales, since the nirK phylogeny was incompatible with the 16S rDNA phylogeny (Heylen et al, 2006;Jones et al, 2008;Philippot et al, 2002;Yoshida et al, 2009). Our results showed that over 80% of NirS clones distributed in clusters I and VI (unknown branch), cluster II (Rhodobacterales).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commmentioning
confidence: 59%
“…However, Saito et al (2008) reported that NirS clones related to Burkholderiales and Rhodocyclales dominated in the rice paddy soil (Saito et al, 2008). A possible reason was that plant communities or the rhizosphere and soil factors could affect the structure and activity of the denitrifying community (Kowalchuk et al, 2002;Philippot et al, 2002). Based on the nosZ clone library analysis, the overwhelming majority of clones (cluster IeIII, and cluster VeVII) were related to Rhizobiales (Brucellaceae, Rhizobiaceae and Bradyrhizobiaceae) and Burkholderiales (Alcaligenaceae, Burkholderiaceae and Oxalobacteraceae) and only few clones in cluster IV were related to Rhodospirillales (Rhodospirillaceae), and the NosZ-based denitrifiers composition from our studied soil was similar to that from other farmland soils (Enwall et al, 2005;Horn et al, 2006).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commmentioning
confidence: 99%
“…Only few non-target sequences occurred and were excluded from further analyses; 95±7% of sequences generated from amplicons obtained with a certain structural gene-specific (that is, narG, nirK, nirS or nosZ) primer set were related to publicly available target genes of that primer set. Such amplification specificity is above or in the range of values obtained for other structural gene marker analyses (for example, average of 87±11% for narG, dsrAB, [FeFe]-hydrogenase and dioxygenase genes; Philippot et al, 2002;Loy et al, 2004;Iwai et al, 2010;Schmidt et al, 2010).…”
Section: Denitrifiers In Cryoturbated and Unturbated Peat K Palmer Et Almentioning
confidence: 69%
“…narG, nirK, nirS and nosZ were amplified using the primer pairs narG1960f (TAYGTSGGSCARGAR-AA)/narG2650r (TTYTCRTACCABGTBGC; Philippot et al, 2002), F1aCu (ATCATGGTSCTGCCGCG)/ R3Cu (GCCTCGATCAGRTTGTGGTT; Throbäck et al, 2004), cd3aF (GTSAACGTSAAGGARACSG G)/R3cd (GASTTCGGRTGSGTCTTGA; Throbäck et al, 2004) and nosZF (CGCTGTTCITCGACAGYC AG)/nosZR (ATGTGCAKIGCRTGGCAGAA; Rich et al, 2003), respectively. Each primer was preceeded by a 6-bp-long barcode (AGCGTC for unturbated and ATATAC for cryoturbated soil samples) to separate sequences after pyrosequencing.…”
Section: Assessment Of Denitrification In Soil Microcosmsmentioning
confidence: 99%
See 1 more Smart Citation